Public pension and household saving: evidence from China - Jin Feng; Lixin He; Hiroshi Sato (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
We relate household saving to pension reform, to explain the high household saving rates in urban China from a new perspective. We use the exogenous - policy induced - variation in pension wealth to explicitly estimate the impact of pension wealth on household saving, and obtain a significant offset effect of pension wealth on household saving. Our estimations show that pension reform boosted the household saving rate in 1999 by about 6 percentage points for cohort aged 25-29 and by about 3 percentage points for cohort aged 50-59. Our results also indicate that declining pension wealth reduces expenditure on education and health more than on other consumption items.
URN:NBN:fi:bof-201408072159
Keywords: H31; H55; P35; 330; pensions; pension reform; household savings rate; China